A polishing liquid for aluminum nitride ceramic substrate and preparation method thereof
By using abrasive mixture of diamond powder, cerium oxide powder and nanosilicon dioxide in the polishing liquid of the aluminum nitride ceramic substrate, and adding graphite powder, dispersant, anti-crystallization agent and thickening agent, the pH value is controlled to 8.6~9.4, the problems of low polishing efficiency of aluminum nitride ceramic substrate and easy crystallization of the polishing liquid in the prior art are solved, and the effect of efficient polishing and stable surface roughness is achieved.
Patent Information
- Application Number
- CN202411991495.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-01
AI Technical Summary
The prior art has problems in the polishing process of aluminum nitride ceramic substrates with low removal rate and easy crystallization of polishing liquid, making it difficult to achieve the requirements of efficient polishing and stable surface roughness.
A mixture of diamond micropowder abrasives, cerium oxide micropowder abrasives and nanosilicon dioxide abrasives is used as the main abrasives, and graphite micropowder, dispersant, anti-crystallizing agent and thickening agent are added to accurately control the pH value to 8.6~9.4 to form an efficient polishing liquid.
The polishing rate of the aluminum nitride ceramic substrate is significantly improved, the surface roughness is reduced, the secondary scratches during the polishing process is reduced, and the stability and service life of the polishing liquid are improved.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of grinding and polishing, and in particular to a polishing liquid for an aluminum nitride ceramic substrate and a preparation method thereof. Background Art
[0002] In the field of ceramic material processing technology, aluminum nitride ceramic substrates are widely used in electronics, aerospace, military and other fields due to their high hardness, high thermal conductivity, low thermal expansion coefficient and good electrical insulation performance. Aluminum nitride ceramic substrates need to undergo a wafer polishing process before application, and the surface damage of the wafer after grinding needs to be removed to achieve the surface roughness and polishing efficiency required by the aluminum nitride ceramic substrate. In general, the surface roughness Ra value of aluminum nitride ceramic substrates should be less than 30nm, and the material removal rate should be in the range of 0.5μm to 2μm per hour.
[0003] Chemical mechanical polishing is currently the most important flattening ultra-precision processing method for aluminum nitride ceramics. However, in this process, due to the high hardness and high brittleness of aluminum nitride ceramics, there are problems such as low removal rate and relatively slow material removal speed during the processing. In addition, the polishing liquid is prone to crystallization due to heat during the polishing process, which will cause secondary scratches or unevenness on the polished surface, making it difficult to achieve the surface roughness and polishing efficiency required for polishing aluminum nitride ceramic substrates. Therefore, how to prepare an efficient and stable polishing liquid to meet the surface roughness and polishing efficiency requirements of aluminum nitride ceramic substrates is an important problem facing current technology.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The present invention provides a polishing liquid for an aluminum nitride ceramic substrate, wherein the polishing liquid is mainly composed of the following components in parts by mass: 6 to 15 parts of mixed abrasive, 3 to 5 parts of graphite powder, 0.6 to 6 parts of dispersant, 0.5 to 6 parts of anti-crystallization agent, 0.1 to 2 parts of thickener, 0.05 to 5 parts of pH regulator, and 100 to 150 parts of deionized water; The pH of the polishing liquid is adjusted to 8.6-9.4 by using a pH adjuster.
[0006] Preferably, the mixed abrasive comprises diamond micro-powder abrasive, cerium oxide micro-powder abrasive and nano-silicon dioxide abrasive.
[0007] More preferably, the mass ratio of the diamond micropowder abrasive, the cerium oxide micropowder abrasive and the nano-silicon dioxide abrasive in the mixed abrasive is 1:4:4 to 3:4:4.
[0008] Further preferably, in the mixed abrasive, the particle size of the diamond micro-powder abrasive is 2 μm-5 μm, the particle size of the cerium oxide micro-powder abrasive is 1 μm-3 μm, and the particle size of the nano-silicon dioxide abrasive is 50 nm-100 nm.
[0009] Preferably, the particle size of the graphite powder is 0.5 μm to 2 μm.
[0010] Preferably, the dispersant is a mixture of polyethylene glycol and hyperbranched polyether.
[0011] More preferably, the mass ratio of the dispersant polyethylene glycol to the hyperbranched polyether is 2:1 to 3:1.
[0012] Preferably, the anti-crystallization agent is a mixture of polyaspartic acid and potassium pyrophosphate.
[0013] More preferably, the mass ratio of the anticrystallization agent polyaspartic acid to potassium pyrophosphate is 1:2 to 2:1.
[0014] Preferably, the thickener includes one or more of sodium carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose and xanthan gum.
[0015] Preferably, the pH adjuster includes one or more of sodium hydroxide, potassium hydroxide, ammonia water, sodium carbonate and hydrochloric acid.
[0016] The present invention also provides a method for preparing a polishing liquid for an aluminum nitride ceramic substrate, the preparation method comprising the following steps: (1) Weigh a certain amount of abrasive according to the proportion and mix them evenly; (2) Weigh a certain amount of graphite powder; (3) Weigh a certain amount of dispersant according to the proportion, add a certain amount of deionized water into a container, heat the deionized water to 60°C~80°C, add the dispersant while stirring, and fully dissolve it to obtain a dispersant solution; (4) Weigh a certain amount of anticrystallization agent according to a certain ratio, add a certain amount of deionized water into a container, add the anticrystallization agent under stirring to fully dissolve the anticrystallization agent, and obtain an anticrystallization agent solution; (5) Weigh a certain amount of thickener, add a certain amount of deionized water into a container, add the thickener under stirring to fully dissolve it, and obtain a thickener solution; (6) Slowly add the mixed abrasive weighed in (1) and the graphite powder weighed in (2) to the dispersant solution prepared in (3). During the addition process, use a high-speed stirrer to stir, the stirrer speed is 1000 r / min~3000 r / min, and the stirring time is 30min~60min; (7) The anti-crystallization agent solution prepared in (4) and the thickener solution prepared in (5) are slowly added to the mixed solution containing abrasive, graphite and dispersant prepared in (6) in sequence. After addition, stirring is continued at a stirring speed of 500-1000 r / min for 20-30 min. (8) Weigh a certain amount of pH adjusting agent and dissolve it in a certain amount of deionized water to obtain a pH adjusting solution. The pH adjusting solution is added to the mixed solution prepared in (7) under stirring to adjust the pH of the mixed solution to 8.6-9.4, thereby obtaining a polishing solution for aluminum nitride ceramic substrates.
[0017] The polishing liquid for the aluminum nitride ceramic substrate provided by the present invention can effectively perform polishing treatment on the aluminum nitride ceramic substrate, improve the polishing rate, significantly reduce the surface roughness, and reduce secondary scratches during the polishing process.
[0018] In the selection of polishing liquid abrasives, the present invention optimizes the ratio and performance of the abrasives, adopts a mixture of diamond micropowder abrasives, cerium oxide micropowder abrasives and nano-silicon dioxide abrasives as the main abrasives, and adjusts the mass ratio of the three abrasives and controls the particle size of the three abrasives, thereby improving the polishing efficiency of the aluminum nitride ceramic substrate and reducing the surface roughness. The mixture of the three abrasives can be used as an abrasive to give full play to the advantages of the three abrasives, produce a synergistic effect, and has the beneficial effects of improving the polishing efficiency, improving the surface quality of the polished workpiece and extending the service life of the polishing liquid. First, when the three abrasives are used together, there is a synergistic effect of material removal. The diamond micropowder first performs efficient material removal, the cerium oxide micropowder assists the softening and pretreatment of the material through chemical action, and the nano-silicon dioxide abrasive finally performs fine treatment on the surface. This synergistic effect can make the polishing efficiency of the aluminum nitride ceramic substrate higher and the surface quality better. Secondly, the three abrasives are mixed and used, and have a synergistic effect of dispersion stability. The particle sizes of the three abrasives are different, the diamond micropowder abrasive particles are relatively large, the cerium oxide micropowder abrasive particles are moderate in size, and the nano-silicon dioxide abrasive particles are the smallest. This difference in particle size contributes to their dispersion stability in the polishing liquid. The larger diamond micro-powder abrasive particles can provide a physical barrier for the smaller nano-silica abrasive particles, preventing the agglomeration of the nano-silica abrasive particles. Again, the three abrasives are used in combination, which has a dynamic balance optimization effect. During the polishing process, the consumption rate of the three abrasives is different. As the polishing progresses, the ratio between the abrasives will change. However, due to their synergistic effect, this change can maintain a good polishing effect within a certain range by complementing the abrasives. In the early stage of polishing, the consumption of diamond micro-powder abrasives and cerium oxide micro-powder abrasives is faster, and at this time they mainly play the role of material removal; as the polishing progresses, the nano-silica abrasive begins to play a more important role, filling the surface defects, so that the polishing process can be continuously optimized, and finally a high-quality polished surface is obtained.
[0019] The invention chooses to add graphite powder to the polishing liquid in order to reduce the crystallization phenomenon during polishing. Graphite powder has good lubrication and thermal conductivity, and can improve the heat exchange and friction conditions during the polishing process, thereby reducing the probability of crystallization.
[0020] In the selection of the dispersant used in the polishing liquid, the present invention adopts a mixture of polyethylene glycol and a hyperbranched polyether as a dispersant, and preferably, the mass ratio of the two dispersants is 2:1~3:1. Mixing polyethylene glycol and hyperbranched polyether as a dispersant can play a synergistic role. Polyethylene glycol (PEG) is a linear polymer with a relatively extended molecular chain. It can interact with the surface of the dispersed abrasive particles through the oxygen atoms in its ether bonds and adsorb on the surface of the abrasive particles. Hyperbranched polyether has a highly branched structure and its molecular shape is approximately spherical. When the two are mixed, the hyperbranched polyether can fill the gaps between the polyethylene glycol molecular chains to form a stable adsorption layer, which can effectively resist the agglomeration of abrasive particles in the polishing liquid, thereby improving the consistency of the polishing effect.
[0021] In the selection of the anti-crystallization agent used in the polishing liquid, the present invention selects a mixture of polyaspartic acid and potassium pyrophosphate as the anti-crystallization agent, preferably, the mass ratio of polyaspartic acid to potassium pyrophosphate is 1:2~2:1. When polyaspartic acid and potassium pyrophosphate exist at the same time, they produce a synergistic effect on the chelation of metal ions. Polyaspartic acid can gather metal ions around it through the adsorption and entanglement of its molecular chain, making it easier for metal ions to contact with the pyrophosphate ions of potassium pyrophosphate. Pyrophosphate ions can form a more complex and more stable chelate structure with these metal ions "captured" by polyaspartic acid. The synergistic effect of polyaspartic acid and potassium pyrophosphate can prevent the generation of crystal nuclei from multiple angles, making it more difficult for metal ions to reach the concentration and state required for crystallization in the solution. Even if a small amount of crystal nuclei are formed, the mixture of polyaspartic acid and potassium pyrophosphate can hinder the growth of crystals. When the polishing liquid is used for a long time, the concentration of metal ions may increase due to reasons such as water evaporation, and there is a tendency to crystallize. At this time, the synergistic effect of polyaspartic acid and potassium pyrophosphate can effectively delay the growth of crystals and maintain the stability of the polishing liquid.
[0022] The present invention accurately controls the pH value of the polishing liquid to 8.6~9.4 for the following considerations: First, controlling the pH value within the range of 8.6~9.4 is conducive to maintaining the stability of the abrasive. Within the pH value range of 8.6~9.4, the chemical stability of diamond micro-powder abrasives, cerium oxide micro-powder abrasives and nano-silicon dioxide abrasives can be well maintained, thereby ensuring the stable performance of their grinding performance. Within the pH range of 8.6~9.4, the surface charge of the abrasive can be maintained in a state that is conducive to dispersion, and agglomeration is not likely to occur, so that the abrasive can be evenly distributed in the polishing liquid, thereby improving the uniformity of polishing. Secondly, for the dispersant composed of polyethylene glycol and polyvinyl alcohol, under the environment of pH value of 8.6~9.4, they can cooperate with each other to maintain their own stability, and can jointly resist some factors that may affect the performance of the dispersant, such as temperature changes, the influence of trace impurities, etc. Thirdly, for the anti-crystallization agent composed of polyaspartic acid and potassium pyrophosphate, the synergistic effect of polyaspartic acid and potassium pyrophosphate can be fully exerted under the condition of pH value of 8.6~9.4. Finally, in the range of pH value of 8.6~9.4, the chemical stability of aluminum nitride ceramic substrate is guaranteed.
[0023] Compared with the prior art, the present invention has the following beneficial effects: 1. High polishing efficiency: The present invention adopts a mixture of diamond micro-powder abrasive, cerium oxide micro-powder abrasive and nano-silicon dioxide abrasive in a specific ratio, which can effectively remove the defects on the surface of the aluminum nitride ceramic substrate and improve the polishing efficiency. At the same time, by optimizing the ratio and performance of graphite micro-powder, dispersant, anti-crystallization agent, thickener and pH regulator, the polishing effect can be further improved, the surface roughness can be reduced, and the secondary damage to the substrate can be reduced.
[0024] 2. Stable polishing effect: In the polishing liquid of the present invention, the amount of abrasive materials and various additives added can be precisely controlled to ensure the stability and repeatability of the polishing effect. This can not only improve production efficiency, but also ensure the quality consistency of the product.
[0025] 3. Wide application scope: Since the polishing liquid of the present invention has the characteristics of high efficiency, stability and environmental protection, it can be widely used in the fields of electronics, aerospace, military and the like, meeting the requirements of different industries for the surface quality of aluminum nitride ceramic substrates.
[0026] In general, compared with the prior art, the present invention has higher polishing efficiency, more stable polishing effect, wider application range, low cost and high benefit, and is an ideal polishing liquid for aluminum nitride ceramic substrates. DETAILED DESCRIPTION
[0027] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased from the market.
[0028] Embodiment 1: This embodiment provides a high-efficiency polishing liquid for an aluminum nitride ceramic substrate and a preparation method thereof, and the specific steps are as follows: (1) Select 6 parts of mixed abrasives, weigh 0.66 parts of diamond micro-powder abrasive with a particle size of 2 μm, 2.67 parts of cerium oxide micro-powder abrasive with a particle size of 1 μm, and 2.67 parts of nano-silicon dioxide abrasive with a particle size of 50 nm, respectively, in a mass ratio of 1:4:4, and mix them evenly; (2) Weigh 3 parts of graphite powder with a particle size of 0.5 μm; (3) Select 0.5 parts of dispersant, and weigh 0.33 parts of dispersant polyethylene glycol and 0.17 parts of hyperbranched polyether in a mass ratio of 2:1. Add 80 parts of deionized water into a container, heat the deionized water to 60°C, add the above dispersant under stirring, and fully dissolve it to obtain a dispersant solution; (4) Select 0.5 parts of anticrystallization agent. According to the mass ratio of 1:2, weigh 0.17 parts of anti-crystallization agent polyaspartic acid and 0.33 parts of potassium pyrophosphate respectively. Add 10 parts of deionized water into a container, add the above anti-crystallization agent under stirring, and make it fully dissolved to obtain an anti-crystallization agent solution; (5) Weigh 0.1 parts of sodium carboxymethyl cellulose as a thickener, add 10 parts of deionized water into a container, add the thickener while stirring, and allow it to fully dissolve to obtain a thickener solution; (6) Slowly add the mixed abrasive weighed in (1) and the graphite powder weighed in (2) to the dispersant solution prepared in (3). During the addition process, stir with a high-speed stirrer at a speed of 1000 r / min for 30 min. (7) The anti-crystallization agent solution prepared in (4) and the thickener solution prepared in (5) are slowly added to the mixed solution containing abrasive, graphite and dispersant prepared in (6) in sequence. After addition, stirring is continued at a stirring speed of 500 r / min for 20 min. (8) Weigh 0.02 parts of sodium hydroxide and dissolve it in 2 parts of deionized water. Weigh 0.03 parts of hydrochloric acid to obtain a pH adjusting solution. Add the pH adjusting solution to the mixed solution prepared in (7) under stirring to adjust the pH of the mixed solution to 8.6 to obtain a polishing solution for aluminum nitride ceramic substrates.
[0029] Embodiment 2: This embodiment provides a high-efficiency polishing liquid for an aluminum nitride ceramic substrate and a preparation method thereof, and the specific steps are as follows: (1) Select 7 parts of mixed abrasives, weigh 0.92 parts of diamond micro-powder abrasive with a particle size of 2 μm, 3.04 parts of cerium oxide micro-powder abrasive with a particle size of 1 μm, and 3.04 parts of nano-silicon dioxide abrasive with a particle size of 60 nm, respectively, in a mass ratio of 1.2:4:4, and mix them evenly; (2) Weigh 3.5 parts of graphite powder with a particle size of 0.7 μm; (3) Select 1 part of dispersant, and weigh 0.68 parts of dispersant polyethylene glycol and 0.32 parts of hyperbranched polyether in a mass ratio of 2.1:1. Add 85 parts of deionized water into a container, heat the deionized water to 70°C, add the above dispersant under stirring, and fully dissolve it to obtain a dispersant solution; (4) Select 1 part of an anti-crystallization agent. According to the mass ratio of 1:1.75, weigh 0.36 parts of anti-crystallization agent polyaspartic acid and 0.64 parts of potassium pyrophosphate respectively. Add 15 parts of deionized water into a container, add the above anti-crystallization agent under stirring, and make it fully dissolved to obtain an anti-crystallization agent solution; (5) Weigh 0.2 parts of sodium carboxymethyl cellulose as a thickener, add 10 parts of deionized water into a container, add the thickener while stirring, and allow it to fully dissolve to obtain a thickener solution; (6) Slowly add the mixed abrasive weighed in (1) and the graphite powder weighed in (2) to the dispersant solution prepared in (3). During the addition process, stir with a high-speed stirrer at a speed of 2000 r / min for 40 min. (7) The anti-crystallization agent solution prepared in (4) and the thickener solution prepared in (5) are slowly added to the mixed solution containing abrasive, graphite and dispersant prepared in (6) in sequence. After addition, stirring is continued at a stirring speed of 600 r / min for 25 min. (8) Weigh 0.1 parts of sodium hydroxide and dissolve it in 5 parts of deionized water to obtain a pH adjusting solution. The pH adjusting solution is added to the mixed solution prepared in (5) under stirring to adjust the pH of the mixed solution to 8.7 to obtain a polishing solution for aluminum nitride ceramic substrates.
[0030] Embodiment 3: This embodiment provides a high-efficiency polishing liquid for an aluminum nitride ceramic substrate and a preparation method thereof, and the specific steps are as follows: (1) 8 parts of mixed abrasives were selected, and 0.96 parts of diamond micro-powder abrasive with a particle size of 3 μm, 3.52 parts of cerium oxide micro-powder abrasive with a particle size of 2 μm, and 3.52 parts of nano-silicon dioxide abrasive with a particle size of 70 nm were weighed respectively in a mass ratio of 1.4:4:4, and then mixed evenly; (2) Weigh 3.5 parts of graphite powder with a particle size of 0.9 μm; (3) Select 2 parts of dispersant, and weigh 1.38 parts of dispersant polyethylene glycol and 0.62 parts of hyperbranched polyether respectively according to the mass ratio of 2.2:1. Add 90 parts of deionized water into a container, heat the deionized water to 80°C, add the above dispersant under stirring, and make it fully dissolved to obtain a dispersant solution; (4) Select 2 parts of anticrystallization agent. According to the mass ratio of 1:1.5, weigh 0.8 parts of anti-crystallization agent polyaspartic acid and 1.2 parts of potassium pyrophosphate respectively. Add 15 parts of deionized water into a container, add the above anti-crystallization agent under stirring, and make it fully dissolved to obtain an anti-crystallization agent solution; (5) Weigh 0.4 parts of thickener hydroxyethyl cellulose, add 10 parts of deionized water into a container, add the thickener while stirring to fully dissolve it, and obtain a thickener solution; (6) Slowly add the mixed abrasive weighed in (1) and the graphite powder weighed in (2) to the dispersant solution prepared in (3). During the addition process, stir with a high-speed stirrer at a speed of 3000 r / min for 60 min. (7) The anti-crystallization agent solution prepared in (4) and the thickener solution prepared in (5) are slowly added to the mixed solution containing abrasive, graphite and dispersant prepared in (6) in sequence. After addition, stirring is continued at a stirring speed of 700 r / min for 30 min. (8) Weigh 0.5 parts of sodium hydroxide and dissolve it in 5 parts of deionized water to obtain a pH adjusting solution. The pH adjusting solution is added to the mixed solution prepared in (5) under stirring to adjust the pH of the mixed solution to 8.8 to obtain a polishing solution for aluminum nitride ceramic substrates.
[0031] Embodiment 4: This embodiment provides a high-efficiency polishing liquid for an aluminum nitride ceramic substrate and a preparation method thereof, and the specific steps are as follows: (1) 9 parts of mixed abrasives were selected, and 0.94 parts of diamond micro-powder abrasive with a particle size of 3 μm, 4.03 parts of cerium oxide micro-powder abrasive with a particle size of 2 μm, and 4.03 parts of nano-silicon dioxide abrasive with a particle size of 70 nm were weighed respectively according to a mass ratio of 1.6:4:4, and then mixed evenly; (2) Weigh 3.5 parts of graphite powder with a particle size of 1 μm; (3) Select 2.5 parts of dispersant, and weigh 1.74 parts of dispersant polyethylene glycol and 0.76 parts of hyperbranched polyether in a mass ratio of 2.3:1. Add 90 parts of deionized water into a container, heat the deionized water to 65°C, add the above dispersant under stirring, and fully dissolve it to obtain a dispersant solution; (4) Select 2.5 parts of anticrystallization agent. According to the mass ratio of 1:1.25, weigh 1.1 parts of anti-crystallization agent polyaspartic acid and 1.4 parts of potassium pyrophosphate respectively. Add 15 parts of deionized water into a container, add the above anti-crystallization agent under stirring, and make it fully dissolved to obtain an anti-crystallization agent solution; (5) Weigh 0.3 parts of thickener hydroxyethyl cellulose and 0.2 parts of sodium carboxymethyl cellulose, add 10 parts of deionized water into a container, add the thickener while stirring, and fully dissolve it to obtain a thickener solution; (6) Slowly add the mixed abrasive weighed in (1) and the graphite powder weighed in (2) to the dispersant solution prepared in (3). During the addition process, stir with a high-speed stirrer at a speed of 3000 r / min for 60 min. (7) The anti-crystallization agent solution prepared in (4) and the thickener solution prepared in (5) are slowly added to the mixed solution containing abrasive, graphite and dispersant prepared in (6) in sequence. After addition, stirring is continued at a stirring speed of 800 r / min for 30 min. (8) Weigh 1 part of potassium hydroxide and dissolve it in 10 parts of deionized water to obtain a pH adjusting solution. The pH adjusting solution is added to the mixed solution prepared in (5) under stirring to adjust the pH of the mixed solution to 8.9 to obtain a polishing solution for aluminum nitride ceramic substrates.
[0032] Embodiment 5: This embodiment provides a high-efficiency polishing liquid for an aluminum nitride ceramic substrate and a preparation method thereof, and the specific steps are as follows: (1) 10 parts of mixed abrasives were selected, and 1.02 parts of diamond micro-powder abrasive with a particle size of 4 μm, 4.49 parts of cerium oxide micro-powder abrasive with a particle size of 2 μm, and 4.49 parts of nano-silicon dioxide abrasive with a particle size of 80 nm were weighed respectively in a mass ratio of 1.8:4:4, and then mixed evenly; (2) Weigh 4 parts of graphite powder with a particle size of 1.2 μm; (3) Select 3 parts of dispersant, and weigh 2.14 parts of dispersant polyethylene glycol and 0.86 parts of hyperbranched polyether in a mass ratio of 2.5:1. Add 100 parts of deionized water into a container, heat the deionized water to 75°C, add the above dispersant under stirring, and fully dissolve it to obtain a dispersant solution; (4) Select 3 parts of anticrystallization agent. According to the mass ratio of 1:1, weigh 1.5 parts of anti-crystallization agent polyaspartic acid and 1.5 parts of potassium pyrophosphate respectively. Add 15 parts of deionized water into a container, add the above anti-crystallization agent under stirring, and make it fully dissolved to obtain an anti-crystallization agent solution; (5) Weigh 1.2 parts of thickener hydroxypropyl methylcellulose, add 10 parts of deionized water into a container, add the thickener while stirring to fully dissolve it, and obtain a thickener solution; (6) Slowly add the mixed abrasive weighed in (1) and the graphite powder weighed in (2) to the dispersant solution prepared in (3). During the addition process, stir with a high-speed stirrer at a speed of 3000 r / min for 60 min. (7) The anti-crystallization agent solution prepared in (4) and the thickener solution prepared in (5) are slowly added to the mixed solution containing abrasive, graphite and dispersant prepared in (6) in sequence. After addition, stirring is continued at a stirring speed of 1000 r / min for 30 min. (8) Weigh 0.5 parts of potassium hydroxide and 0.5 parts of sodium hydroxide, and dissolve them in 10 parts of deionized water to obtain a pH adjusting solution. The pH adjusting solution is added to the mixed solution prepared in (5) under stirring to adjust the pH of the mixed solution to 9.0, thereby obtaining a polishing solution for aluminum nitride ceramic substrates.
[0033] Embodiment 6: This embodiment provides a high-efficiency polishing liquid for an aluminum nitride ceramic substrate and a preparation method thereof, and the specific steps are as follows: (1) 11 parts of mixed abrasives were selected, and 2.2 parts of diamond micro-powder abrasive with a particle size of 4 μm, 4.4 parts of cerium oxide micro-powder abrasive with a particle size of 2 μm, and 4.4 parts of nano-silicon dioxide abrasive with a particle size of 90 nm were weighed respectively in a mass ratio of 1:2:2, and then mixed evenly; (2) Weigh 4 parts of graphite powder with a particle size of 1.4 μm; (3) Select 4 parts of dispersant, and weigh 2.92 parts of dispersant polyethylene glycol and 1.08 parts of hyperbranched polyether respectively according to the mass ratio of 2.7:1. Add 100 parts of deionized water into a container, heat the deionized water to 80°C, add the above dispersant under stirring, and make it fully dissolved to obtain a dispersant solution; (4) Select 4 parts of anticrystallization agent. According to the mass ratio of 1.25:1, weigh 2.2 parts of anti-crystallization agent polyaspartic acid and 1.8 parts of potassium pyrophosphate respectively. Add 20 parts of deionized water into a container, add the above anti-crystallization agent under stirring, and make it fully dissolved to obtain an anti-crystallization agent solution; (5) Weigh 1.5 parts of thickener hydroxypropyl methylcellulose, add 10 parts of deionized water into a container, add the thickener while stirring to fully dissolve it, and obtain a thickener solution; (6) Slowly add the mixed abrasive weighed in (1) and the graphite powder weighed in (2) to the dispersant solution prepared in (3). During the addition process, stir with a high-speed stirrer at a speed of 3000 r / min for 50 min. (7) The anti-crystallization agent solution prepared in (4) and the thickener solution prepared in (5) are slowly added to the mixed solution containing abrasive, graphite and dispersant prepared in (6) in sequence. After addition, stirring is continued at a stirring speed of 1000 r / min for 30 min. (8) Weigh 1.5 parts of sodium carbonate and dissolve it in 10 parts of deionized water to obtain a pH adjusting solution. The pH adjusting solution is added to the mixed solution prepared in (5) under stirring to adjust the pH of the mixed solution to 9.1 to obtain a polishing solution for aluminum nitride ceramic substrates.
[0034] Embodiment 7: This embodiment provides a high-efficiency polishing liquid for an aluminum nitride ceramic substrate and a preparation method thereof, and the specific steps are as follows: (1) 12 parts of mixed abrasives were selected, and 2.76 parts of diamond micro-powder abrasive with a particle size of 4 μm, 4.62 parts of cerium oxide micro-powder abrasive with a particle size of 3 μm, and 4.62 parts of nano-silicon dioxide abrasive with a particle size of 90 nm were weighed respectively in a mass ratio of 1.2:2:2, and then mixed evenly; (2) Weigh 4.5 parts of graphite powder with a particle size of 1.6 μm; (3) Select 4.5 parts of dispersant, and weigh 3.32 parts of dispersant polyethylene glycol and 1.18 parts of hyperbranched polyether in a mass ratio of 2.8:1. Add 100 parts of deionized water into a container, heat the deionized water to 70°C, add the above dispersant under stirring, and fully dissolve it to obtain a dispersant solution; (4) Select 4.5 parts of anticrystallization agent. According to the mass ratio of 1.5:1, weigh 2.7 parts of anti-crystallization agent polyaspartic acid and 1.8 parts of potassium pyrophosphate respectively. Add 20 parts of deionized water into a container, add the above anti-crystallization agent under stirring, and make it fully dissolved to obtain an anti-crystallization agent solution; (5) Weigh 1.7 parts of xanthan gum as a thickener, add 10 parts of deionized water into a container, add the thickener while stirring to fully dissolve it, and obtain a thickener solution; (6) Slowly add the mixed abrasive weighed in (1) and the graphite powder weighed in (2) to the dispersant solution prepared in (3). During the addition process, stir with a high-speed stirrer at a speed of 2000 r / min for 60 min. (7) The anti-crystallization agent solution prepared in (4) and the thickener solution prepared in (5) are slowly added to the mixed solution containing abrasive, graphite and dispersant prepared in (6) in sequence. After addition, stirring is continued at a stirring speed of 1000 r / min for 30 min. (8) Weigh 2 parts of ammonia water and dissolve it in 10 parts of deionized water to obtain a pH adjusting solution. The pH adjusting solution is added to the mixed solution prepared in (5) under stirring to adjust the pH of the mixed solution to 9.2 to obtain a polishing solution for aluminum nitride ceramic substrates.
[0035] Embodiment 8: This embodiment provides a high-efficiency polishing liquid for an aluminum nitride ceramic substrate and a preparation method thereof, and the specific steps are as follows: (1) 14 parts of mixed abrasives were selected, and 3.32 parts of diamond micro-powder abrasive with a particle size of 5 μm, 5.34 parts of cerium oxide micro-powder abrasive with a particle size of 3 μm, and 5.34 parts of nano-silicon dioxide abrasive with a particle size of 100 nm were weighed respectively according to a mass ratio of 2.5:4:4, and then mixed evenly; (2) Weigh 4.5 parts of graphite powder with a particle size of 1.8 μm; (3) Select 5 parts of dispersant, and weigh 3.72 parts of dispersant polyethylene glycol and 1.28 parts of hyperbranched polyether respectively according to the mass ratio of 2.9:1. Add 100 parts of deionized water into a container, heat the deionized water to 65°C, add the above dispersant under stirring, and make it fully dissolved to obtain a dispersant solution; (4) Select 5 parts of anticrystallization agent. According to the mass ratio of 1.75:1, weigh 3.18 parts of anti-crystallization agent polyaspartic acid and 1.72 parts of potassium pyrophosphate respectively. Add 20 parts of deionized water into a container, add the above anti-crystallization agent under stirring, and make it fully dissolved to obtain an anti-crystallization agent solution; (5) Weigh 1 part of thickener xanthan gum and 1 part of hydroxypropyl methylcellulose, add 15 parts of deionized water into a container, add the thickener while stirring to fully dissolve it, and obtain a thickener solution; (6) Slowly add the mixed abrasive weighed in (1) and the graphite powder weighed in (2) to the dispersant solution prepared in (3). During the addition process, stir with a high-speed stirrer at a speed of 2000 r / min for 60 min. (7) The anti-crystallization agent solution prepared in (4) and the thickener solution prepared in (5) are slowly added to the mixed solution containing abrasive, graphite and dispersant prepared in (6) in sequence. During the addition process, a high-speed stirrer is used for stirring. The stirrer speed is 3000 r / min and the stirring time is continued for 60 min. (8) Weigh 2 parts of sodium carbonate and 1 part of sodium hydroxide, and dissolve them in 10 parts of deionized water to obtain a pH adjusting solution. The pH adjusting solution is added to the mixed solution prepared in (5) under stirring to adjust the pH of the mixed solution to 9.3, thereby obtaining a polishing solution for aluminum nitride ceramic substrates.
[0036] Embodiment 9: This embodiment provides a high-efficiency polishing liquid for an aluminum nitride ceramic substrate and a preparation method thereof, and the specific steps are as follows: (1) 15 parts of mixed abrasives were selected, and 4.08 parts of diamond micro-powder abrasive with a particle size of 5 μm, 5.46 parts of cerium oxide micro-powder abrasive with a particle size of 3 μm, and 5.46 parts of nano-silicon dioxide abrasive with a particle size of 100 nm were weighed respectively in a mass ratio of 3:4:4, and then mixed evenly; (2) Weigh 5 parts of graphite powder with a particle size of 2 μm; (3) Select 6 parts of dispersant, and weigh 4.5 parts of dispersant polyethylene glycol and 1.5 parts of hyperbranched polyether in a mass ratio of 3:1. Add 100 parts of deionized water into a container, heat the deionized water to 80°C, add the above dispersant under stirring, and fully dissolve it to obtain a dispersant solution; (4) Select 6 parts of anticrystallization agent. According to the mass ratio of 2:1, weigh 4 parts of anti-crystallization agent polyaspartic acid and 2 parts of potassium pyrophosphate respectively. Add 25 parts of deionized water into a container, add the above anti-crystallization agent under stirring, and make it fully dissolved to obtain an anti-crystallization agent solution; (5) Select 2 parts of thickener. Weigh 0.5 parts of xanthan gum, 1 part of hydroxyethyl cellulose and 0.5 parts of hydroxypropyl methyl cellulose respectively, add 15 parts of deionized water into a container, add the thickener while stirring, and fully dissolve it to obtain a thickener solution; (6) Slowly add the mixed abrasive weighed in (1) and the graphite powder weighed in (2) to the dispersant solution prepared in (3). During the addition process, stir with a high-speed stirrer at a speed of 3000 r / min for 60 min. (7) The anti-crystallization agent solution prepared in (4) and the thickener solution prepared in (5) are slowly added to the mixed solution containing abrasive, graphite and dispersant prepared in (6) in sequence. After addition, stirring is continued at a stirring speed of 1000 r / min for 30 min. (8) Weigh 5 parts of sodium carbonate and dissolve it in 10 parts of deionized water to obtain a pH adjusting solution. The pH adjusting solution is added to the mixed solution prepared in (5) under stirring to adjust the pH of the mixed solution to 9.4 to obtain a polishing solution for aluminum nitride ceramic substrates.
[0037] Comparative Example 1: This comparative example provides a polishing liquid for an aluminum nitride ceramic substrate and a preparation method thereof, and the specific steps are as follows: (1) Weigh 25 parts of silica abrasive with a particle size of 150 nm; (2) Weigh 10 parts of polyethylene glycol as a dispersant; add 90 parts of deionized water into a container, and add the above dispersant under stirring to obtain a dispersion; (3) Weigh 7 parts of anticrystallization agent ethylenediaminetetraacetic acid (EDTA), add 15 parts of deionized water into a container, add the above anticrystallization agent under stirring to fully dissolve it, and obtain an anticrystallization agent solution; (4) Slowly add the mixed abrasive weighed in (1) to the dispersant solution prepared in (2). During the addition process, stir with a high-speed stirrer at a speed of 1000 r / min for 60 min. (5) Slowly add the anti-crystallization agent solution prepared in (3) to the mixed solution containing abrasive and dispersant prepared in (4). After addition, continue stirring at a stirring speed of 500 r / min for 20 min. (6) Weigh 5 parts of sodium hydroxide and dissolve it in 10 parts of deionized water to obtain a pH adjusting solution. The pH adjusting solution is added to the mixed solution prepared in (4) under stirring until the pH value reaches 11 to obtain a polishing solution for aluminum nitride ceramic substrates.
[0038] Experimental example: Polishing experiments were conducted using the polishing liquids of Examples 1 to 9 and the comparative example: an aluminum nitride ceramic substrate that had been roughly ground with a 20 μm silicon carbide grinding liquid and had a thickness difference within 3 μm was selected. The aluminum nitride substrate was adhered to the ceramic plate using solid wax, and the prepared polishing liquid was dripped onto the polyurethane polishing pad using a peristaltic pump. The polishing pressure was 250 g / cm 2 , the rotation speed is 60rpm, and the polishing time is 1h; the results are shown in the table.
[0039] Table 1 Polishing effect Examples and Comparative Examples Polishing rate Surface Ra (nm) Example 1 0.9μm / h 15 Example 2 1.1μm / h 16 Example 3 1.2μm / h 14 Example 4 1.4μm / h 13 Example 5 1.4μm / h 14 Example 6 1.5μm / h 15 Example 7 1.6μm / h 18 Example 8 1.7μm / h 19 Example 9 1.9μm / h 20 Comparative Example 1 0.4μm / h 40 From the polishing effect, it can be seen that in Examples 1 to 9, the aluminum nitride ceramic substrate is polished according to the technical solution provided by the present invention, and the surface roughness Ra value is between 15nm and 20nm; the material removal rate is in the range of 0.9μm to 1.9μm per hour. The surface roughness and polishing efficiency required for the aluminum nitride ceramic substrate can be achieved. However, the technical solution used in the comparative example exceeds the technical scope provided by the present invention, and in the results of polishing the aluminum nitride ceramic substrate, the polishing efficiency and surface roughness do not meet the requirements.
[0040] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A polishing liquid for an aluminum nitride ceramic substrate, characterized in that: It is mainly composed of the following components by mass: 6 to 15 parts of mixed abrasive, 3 to 5 parts of graphite powder, 0.5 to 6 parts of dispersant, 0.5 to 6 parts of anti-crystallization agent, 0.1 to 2 parts of thickener, 0.05 to 5 parts of pH regulator, and 100 to 150 parts of deionized water; The pH of the polishing liquid is adjusted to 8.6-9.4 by using a pH adjuster.
2. The polishing liquid for aluminum nitride ceramic substrate according to claim 1, characterized in that: The mixed abrasive comprises diamond micro-powder abrasive, cerium oxide micro-powder abrasive and nano silicon dioxide abrasive.
3. The polishing liquid for aluminum nitride ceramic substrate according to claim 2, characterized in that: The mass ratio of the diamond micro-powder abrasive, the cerium oxide micro-powder abrasive and the nano-silicon dioxide abrasive in the mixed abrasive is 1:4:4 to 3:4:4; Preferably, in the mixed abrasive, the particle size of the diamond micro-powder abrasive is 2 μm-5 μm, the particle size of the cerium oxide micro-powder abrasive is 1 μm-3 μm, and the particle size of the nano-silicon dioxide abrasive is 50 nm-100 nm.
4. The polishing liquid for aluminum nitride ceramic substrate according to claim 1, characterized in that: The particle size of the graphite powder is 0.5 μm to 2 μm.
5. The polishing liquid for aluminum nitride ceramic substrate according to claim 1, characterized in that: The dispersant is a mixture of polyethylene glycol and hyperbranched polyether; Preferably, the mass ratio of the dispersant polyethylene glycol to the hyperbranched polyether is 2:1 to 3:
1.
6. The polishing liquid for aluminum nitride ceramic substrate according to claim 1, characterized in that: The anti-crystallization agent is a mixture of polyaspartic acid and potassium pyrophosphate.
7. The polishing liquid for aluminum nitride ceramic substrate according to claim 6, characterized in that: The mass ratio of polyaspartic acid to potassium pyrophosphate in the anti-crystallization agent is 1:2 to 2:
1.
8. The polishing liquid for aluminum nitride ceramic substrate according to claim 1, characterized in that: The thickener includes one or more of sodium carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose and xanthan gum.
9. The polishing liquid for aluminum nitride ceramic substrate according to claim 1, characterized in that: The pH regulator includes one or more of sodium hydroxide, potassium hydroxide, ammonia water, sodium carbonate and hydrochloric acid.
10. The method for preparing a polishing liquid for an aluminum nitride ceramic substrate according to any one of claims 1 to 9, characterized in that: The following steps are involved: (1) Weigh a certain amount of abrasive according to the proportion and mix them evenly; (2) Weigh a certain amount of graphite powder; (3) Weigh a certain amount of dispersant according to the proportion, add a certain amount of deionized water into a container, heat the deionized water to 60°C~80°C, add the dispersant while stirring, and fully dissolve it to obtain a dispersant solution; (4) Weigh a certain amount of anticrystallization agent according to a certain ratio, add a certain amount of deionized water into a container, add the anticrystallization agent under stirring to fully dissolve the anticrystallization agent, and obtain an anticrystallization agent solution; (5) Weigh a certain amount of thickener, add a certain amount of deionized water into a container, add the thickener under stirring to fully dissolve it, and obtain a thickener solution; (6) Slowly add the mixed abrasive weighed in (1) and the graphite powder weighed in (2) to the dispersant solution prepared in (3). During the addition process, use a high-speed stirrer to stir, the stirrer speed is 1000 r / min~3000 r / min, and the stirring time is 30min~60min; (7) The anti-crystallization agent solution prepared in (4) and the thickener solution prepared in (5) are slowly added to the mixed solution containing abrasive, graphite and dispersant prepared in (6) in sequence. After addition, stirring is continued at a stirring speed of 500 to 1000 r / min for 20 to 30 min. (8) Weigh a certain amount of pH adjusting agent and dissolve it in a certain amount of deionized water to obtain a pH adjusting solution. The pH adjusting solution is added to the mixed solution prepared in (7) under stirring to adjust the pH of the mixed solution to 8.6-9.4, thereby obtaining a polishing solution for aluminum nitride ceramic substrates.
Citation Information
Cited By
Polishing solution for polishing ultrahigh-hardness aluminum oxide ceramics
CN121182377A
Monocrystal diamond polishing solution for polishing high-thermal-conductivity aluminum nitride ceramic substrate
CN122357006A